EFEKTIVITAS EARLY PHYSICAL ACTIVITY SETELAH TOTAL KNEE ARTHROPLASTY TERHADAP FUNGSIONAL AKTIVITAS PASIEN - Saputra, Rinaldi Prima; Widagdo, Henry; Sari, Rina Mayang; Helmi, Dio Septiyan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The decision to undergo Total Knee Arthroplasty is not an easy one; patients need courage to undergo TKA. Chronic osteoarthritis complaints of more than grade 2 severely limit an individual's daily activities, and Joint arthroplasty is performed to enhance health-related quality of life in patients with end-stage hip or knee OA. Interestingly, no patient attained a higher level of physical activity 5 years post-surgery compared to their preoperative expectations. Possible reasons for this unmet expectation include other unrealistic expectations, deficiencies in lower extremity functional rehabilitation after TKA, and difficulties in accurately describing and reporting the amount of physical activity in daily life. The type of research used is quasi-experimental with a two-group pretest-posttest design. Sampling used an acidental This study involved 40 respondents as samples. Data analysis was conducted using Paired T-Test and Independent T-Test methods. The study results indicated that both groups had an impact on functional ability. (p<0.000) intervention treatment with the TUG test and (p<0.216) control treatment, so on the sit to stand test, intervention treatment (p<0.000) and (p<0.003) in the control group, but the intervention treatment was proven to improve the average score better also on functional ability using the TUG test compared to the control group (2 vs 1.05) also (2.2 vs 0.95). on the sit to stand test. It is recommended to physiotherapists to apply early activity training to improve functional activity in post-TKA patients with a time span of 3-6 months. Keywords: total knee arthroplasty, early physical activity, functional activity